PRESCRIPTION OF ACTIONS FOR ANNULMENT REFERRING TO IRREGULAR ADMINISTRATIVE ACTS AT THE FEDERAL LEVEL: STATE OF THE ART AND PERSPECTIVES OF CHANGE (Forum, 2021)
Statute of limitations related to the public administration’s prerogative of reviewing, reversing, modifying or substituting administrative decisions from the past are not expressly set forth in the law.Finding a solution on this matter requires previous consideration of several issues regarding the interpretation of the law, all of which show similar complexity and relevance.In particular, the question about whether any statute of limitations may apply to this prerogative with respect to prior administrative decisions that are invalid on absolute grounds, and if so, what is the term of that statutory limitation, has been answered by the National Supreme Court of Justice in old judiciary decisions, by compellingly establishing that no limitation period proceeds over that kind of legal action.Scholars have claimed that the fundamentals of such conclusion are of difficult conciliation with the lawful regulations on the matter, and even with the stare decisis within the Supreme Court itself, concerning, on one hand, common legal practice in the process of interpreting the law –general law just as much as those particularly referred to administrative law– and, on the other, with the social relevance of statutory limitation, including those controversies involving the state as a party. The robustness and persuasive potential of the Supreme Court’s approach contrary to the prevailing judgments allows one to wonder whether the rationales of no legal timeframe was sought by the Court for reasons beyond those strictly legal.Although recent legislative reforms and changes in the case law had occurred on this particular field –reinforcing and confirming that Supreme Court’s traditional view mainly sustained in the private law–, the doubt on the possibility –or even the convenience– of applying that legal doctrine when ruling on cases concerning the public administration’s reversing prerogative remains open.
Keywords: Statute of limitations; Administrative decisions; Invalidity on absolute grounds; Public administration’s reversing prerogative; Law interpretation